The scope of the application of the Consumer Protection Act 68 of 2008 in the context of the sale of defective goods in comparative perspective - De Stadler, Elizabeth Briers (Department of Commercial Law, 2018)
The Consumer Protection Act 68 ('the CPA') came into effect on 31 March 2011. In broad terms, the purpose of the CPA is to promote the social and economic welfare of consumers. Specific reference is made to reducing disadvantages suffered by vulnerable consumers. The question posed in this thesis is whether the scope of the application of the CPA in relation to transactions for goods is consistent with the purpose of the Act, but also how it compares to the approaches taken in the European Union, United Kingdom and Australia. It is argued that the application provisions are not always fair, rational, clear, efficient and consistent with reasonable expectations. The following issues relating to the application of the Act are addressed: the approach to the protection of small juristic persons, the omission of a exclusion based on the purposes for which the transaction is concluded, the onus of proof, the exclusion of transactions outside the ordinary course of business, the definition of 'supplier', whether transactions should be 'for consideration' in order for the consumer to qualify for protection, whether the whole supply chain should be liable and whether all goods should fall within the scope of the Act. Recommendations on these issues are made in light of rationales for consumer protection legislation, proposed criteria for evaluating such legislation (namely whether the legislation is fair, rational, clear, efficient and consistent with reasonable expectations) and comparative research. Suggested amendments to the wording of relevant sections in the Act are made in the final chapter.